The Impact of Political Stability and Violence on The Libyan Trade Balance (Economic studies journal, 2023)
This paper aims to analyses and study the impact of political stability and violence on the Libyan trade balance. To achieve this, a model was built based on the general equilibrium identity in the Libyan economy to measure the impact of political stability and violence on the Libyan trade balance. And by applying the methodology of Autoregressive distributed lagged Model (ARDL) for the period from 1986 to 2017. The results showed the high relative importance of the political stability and violence variable in explaining the changes in the Libyan trade balance, especially in the long term. In addition to the variables of the size of the domestic market, government spending, government revenue, the exchange rate of the Libyan dinar against the US dollar, and inflation in explaining the changes that occur in the Libyan trade balance. In general, the deterioration of the political, security and social conditions, armed conflicts, institutional division, and the governmental transitional period and its extension do not lead to an improvement in the economic environment of the state, and its results are in hindering the implementation and application of economic recovery tools to reach economic well-being. The Libyan parties must take into account the consequences of political and violence and security instability on the future of the Libyan economy
Keywords: Political Stability and Violence; Trade Balance; Macroeconomics; Autoregressive distributed lagged Model (ARDL)